Grand challenges in sex differences in immunology: problems the field must solve before biological sex can guide clinical practice - Katie L. Flanagan; Susan Kovats (Frontiers in Immunology, 2026)
Male and female immune systems differ in composition and function across the entire life course, shaping susceptibility to infection, autoimmunity, allergy, neurodegeneration, cancer, and responses to vaccines and immunotherapies. Despite decades of observational evidence, mechanistic clarity on why these differences arise - and how to exploit them therapeutically - remains limited. This paper outlines six grand challenges that, if addressed, would move sex-differential immunology from description toward clinical application: (1) rigorous identification of the sex differences in immune cell function across the lifespan during health and disease; (2) defining the functional roles of X- and Y-linked immune genes and the impact of X chromosome inactivation escape; (3) mapping the role of sex steroids including their contribution to sex-specific epigenetic regulation; (4) clarifying the immunological impact of the bidirectional sex–microbiota–immunity axis; (5) ensuring that experimental models and study designs make sex a variable rather than a confounder; and (6) translating mechanistic insights into sex-tailored disease prevention and treatment. Progress on these fronts could improve outcomes for both sexes across infectious disease, autoimmunity, allergy, neurodegeneration, cancer, and vaccinology.